(untitled) (El Hilo de la Fabula, 2022)
In this paper we aim to reflect on general issues in the translation of ancient classical texts, particularly Greek theater -given their nature as scripts intended for the stage-. At the same time, based on our experience as translators of Aristophanes, as well as on the testimonies of other translators of the same author, we will point out a series of difficulties -not exhaustive-, when transposing the Aristophanic language into Spanish, including, puns, speaking names, obscene lexicon, colloquialisms, mentions to the events and characters of his time.